Meaning In Life And Hope Among Young Adults With Cancer In Malaysia - Sabri, Nursahira Sahiba Mohd (2024)
Having a sense of meaning and hope has been linked to better health, quality of life, and daily functioning. However, seeking meaning and preserving hope following a cancer diagnosis can be difficult, particularly for young adults with cancer. The purpose of this study was to investigate how young adults with cancer sought meaning and hope and how these two elements influenced their cancer journey. This qualitative study employed a phenomenological approach, which involved the participation of fourteen young adults diagnosed with cancer that recruited from a closed Facebook group. These young adults ranged from 20 to 39 years in age, and their survival years ranged from 1 to 18 years. Semi-structured interviews and a thematic analysis were performed to identify the major themes that emerged from these interviews. The findings revealed that the majority of young people with cancer in this population found positive meaning in their illness, and they perceived cancer from a religious perspective. Religion served as a source of comfort, and it provided them with inner strength during times of suffering. Young adults expressed hopes for helping cancer patients, good physical and mental health, and an ease in afterlife. Their cultural and religious beliefs determined the various forms of hope and subsequently, how hope affected their experiences with cancer. This study observed that not all positive communication with physicians resulted in hope.